The effect of inspiratory and expiratory loads on abdominal muscle activity during breathing in subjects “at risk” for the development of chronic obstructive pulmonary disease and healthy - Mesquita Montes, António (2019)
The abdominal muscle activity has been shown to be variable in subjects with chronic obstructive pulmonary disease (COPD) when respiratory demand increases and their recruitment pattern may change the mechanics, as well as the work and cost of breathing. The scientific evidence in subjects "at risk" for the development of COPD may be important to understand the natural history of this disease. This study aims to evaluate the effect of inspiratory and expiratory loads on the abdominal muscle activity during breathing in subjects "at risk" for the development of COPD and healthy. Thirty-one volunteers, divided in "At Risk" for COPD (n=17; 47.71±5.11years) and Healthy (n=14; 48.21±6.87years) groups, breathed at the same rhythm without load and with 10% of the maximal inspiratory or expiratory pressures, in standing. Surface electromyography was performed to assess the activation intensity of rectus abdominis (RA), external oblique and transversus abdominis/internal oblique (TrA/IO) muscles, during inspiration and expiration. During inspiration, in "At Risk" for COPD group, RA muscle activation was higher with loaded expiration (p=0.016); however, in Healthy group it was observed a higher activation of external oblique and TrA/IO muscles (p<0.050). During expiration, while in "At Risk" for COPD group, RA muscle activation was higher with loaded inspiration (p=0.009), in Healthy group TrA/IO muscle showed a higher activation (p=0.025). Subjects "at risk" for the development of COPD seemed to have a specific recruitment of the superficial layer of ventrolateral abdominal wall for the mechanics of breathing.